2022
DOI: 10.1097/scs.0000000000008603
|View full text |Cite
|
Sign up to set email alerts
|

Schneiderian Membrane Regeneration After Lateral Bony Window Repositioning in Modified Endoscopic-Assisted Maxillary Sinus Surgery: Transmission Electron Microscopy Evaluation

Abstract: : Mandibular reconstruction is one of the most complex procedures concerning the patient’s postoperative facial shape and occlusion condition. In this study, the authors integrated mixed reality, three-dimensional (3D) printing, and robotic-assisted navigation technology to complete the mandibular reconstruction in a novel and more accurate way. Mixed reality can visualize the significant anatomical structures of the operative area, but only be used in simulated operation by now. Three-dimensional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…The main advantage of MESS is that the physiological functions of paranasal sinus are maintained while avoiding the formation of postoperative maxillary cysts or sinus scar tissues 7. A previous study by Han et al9 demonstrated the successful outcomes of MESS through histopathologic and ultrastructural findings indicating the regeneration of SM and complete bone healing with clinical restoration of maxillary sinus functions that were achieved optimally 6 months after the treatment 9. Periodic radiographs and clinical follow-ups are important to ensure that the maxillary sinus is normalized before proceeding with implant treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of MESS is that the physiological functions of paranasal sinus are maintained while avoiding the formation of postoperative maxillary cysts or sinus scar tissues 7. A previous study by Han et al9 demonstrated the successful outcomes of MESS through histopathologic and ultrastructural findings indicating the regeneration of SM and complete bone healing with clinical restoration of maxillary sinus functions that were achieved optimally 6 months after the treatment 9. Periodic radiographs and clinical follow-ups are important to ensure that the maxillary sinus is normalized before proceeding with implant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Rare but several cases of esophageal and pharyngeal perforation due to migration and extrusion of screw have been reported. 2,3,9 On the patient's first visit to hospital due to dysphagia, there was no plate migration on radiologic findings with lateral neck x-ray at extension or flexion view. There was no abnormal hypopharynx posterior wall mucosal finding either.Retropharyngeal granulation is also one of rare complications in ACS surgery.…”
mentioning
confidence: 97%
“…The per-oral TAA implemented in this study minimized the amount of bone removed using an optical navigation system, minimized complications, and maximized bone healing and regeneration of the Schneiderian membrane by repositioning the bony window. 8 In addition, this approach allows a wide field of view and operation of instruments, enabling faster surgery and more efficient operation for surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…5 There is no consensus regarding mandibular bone surgical margins that should be planned to ensure a safe oncologic outcome. In 1988, McGregor and MacDonald 6 recommended planning a clinical resection of 0.5 to 1.0 cm of unaffected bone around the tumor and, more recently, 3 separate groups-Namin et al, 7 Wysluch et al, 8 and Weitz et al 9 -report resection of at least 1.0 cm of uninvolved bone, as measured from either macroscopic tumor or suspected bone involvement. In the preoperative assessment, a computerized tomography (CT) scan, a positron emission tomography CT and eventually an magnetic resonance imaging are performed.…”
Section: Surgical Margins In 3d Planned Mandibular Resections For Squ...mentioning
confidence: 99%
“…Regeneration of the Schneiderian membrane and restoration of the physiologic function of the maxillary sinus are essential for the successful treatment of odontogenic maxillary sinusitis. 7 In 66 patients, Han performed modified endoscopic sinus surgery with repositioning of the lateral bony window for the treatment of odontogenic maxillary sinusitis. Histologically, in the inflamed maxillary sinus membrane, squamous metaplasia was observed with infiltration of inflammatory cells including neutrophils, eosinophils, and plasma cells.…”
Section: Regeneration Of the Mucosal Lining (Schneiderian Membrane) O...mentioning
confidence: 99%